The nightfolk: Ibn 'Arabi behind the veil of night - Rašić, Dunja (University of California Press, 2025)
"This story begins with a divine unveiling: in 1220, a mysterious youth took the Sufi philosopher Muhyi al-Din Ibn 'Arabi behind the veil of the night. There, Ibn 'Arabī first came face to face with advanced and morally ambiguous spiritual practitioners known as the Nightfolk. In The Nightfolk, Duja Rasic offers a pioneering historical and conceptual analysis of the once-widespread beliefs about the night and its people in Muslim cultures and societies. Drawing on a wealth of primary source materials, Rašić traces these beliefs from their origins in the seventh century to their most prominent form in the thirteenth-century works of Ibn 'Arabi. Re-examining common notions of spiritual authority, ascension, self-isolation, moral choice, and transgression in Muslim cultures and societies, The Nightfolk is a crucial read for those interested in philosophical Sufism and Ibn 'Arabi's attempts to bridge the gap between the visible world and the realms of the unseen"--